The net stable funding ratio requirement when money is endogenous - Karlo Kauko (Bank of Finland, 2015)
The NSFR regulation reduces banks' liquidity risks by encouraging the use of deposit funding. Deposit money is created by lending, but the requirement restricts possibilities to grant loans. This contradiction may be destabilising if there is a substantial foreign debt.
URN:NBN:fi:bof-201501261013
Keywords: E51; G21; G28; 330; net stable funding ratio; endogenous money; liquidity regulation